Feasibility of Find cases Actively, Separate safely and Treat effectively (FAST) strategy for early diagnosis of TB in Nepal: An implementation research - Sagun Paudel (Public Library of Science (PLoS), 2021)
Introduction Tuberculosis is one of the leading causes of death worldwide. Diagnosing TB in an early stage and initiating effective treatment is one of the best ways to reduce the burden of tuberculosis. Feasibility of Find cases Actively, Separate safely and Treat effectively (FAST) Strategy helps to improve the early diagnosis of tuberculosis cases among inpatient settings as well as out patient department patients and prevent TB transmission in hospital. This study aimed to assess the feasibility of the FAST strategy, organizational factors, technical factors, barriers and enablers for the proper implementation of the FAST strategy in Nepal. Methods A qualitative study was conducted from April 2019 to August 2019. Data was collected by using focus group discussion, key informant interviews, and client exit interviews. A retrospective research was conducted in different hospitals in Nepal where FAST strategy was implemented. The patients, health care workers, province, district, and National level stakeholders were interviewed. Thematic analysis was used to assess the feasibility as well as barriers and enablers of the FAST strategy. Results Study identified that the ‘current setting’ of implementation and service delivery arrangement at hospitals were not well arranged as per requirements. The research findings showed hospital ownership is crucial for mobilizing staff and proper space management inside hospitals. Study identified that unavailability of a separate room, limited capacity of GeneXpert machine, irregular supply of GeneXpert cartridge, and insufficient human resources for screening and counseling are the major barriers of FAST implementation in Nepal. Conclusion FAST strategy is feasible to implement in healthcare settings in Nepal although the technical and organizational factors should be managed to ensure effective function of the strategy as per the approach. Hospital ownership is essential to mobilize health workers, improve client flow system and proper space management for FAST services.